Exploring how Professional Associations Influence Health System Transformation: The Case of Ontario Health Teams - Alyssa Indar; James Wright; Michelle Nelson (International Journal of Integrated Care, 2023)
Introduction: Health care system transformations that align with the principles of integrated care require the collaborative efforts of various macro-, meso- and micro-level stakeholders. Understanding the roles of various system actors can improve collaboration in ways that support purposeful health system change. Professional associations (PAs) have considerable influence, but little is known about the strategies they use to influence health system transformation. Methods: Using a qualitative descriptive approach, eight interviews with 11 senior level leaders from local PAs were conducted to learn about the strategies used to influence the province-wide reorganization of health care into Ontario Health Teams. Results: During times of health system transformation, PAs balance: (1) supporting members, (2) negotiating with government, (3) collaborating with stakeholders, and (4) reflecting on their role. The enactment of these various functions demonstrates the strategic nature of PAs, and showcases their ability to evolve in ways that align with the dynamic nature of healthcare. Discussion: PAs are highly connected groups, deeply engaged with their members and regularly engaged with other key stakeholders and decision-makers. PAs play a critical role in influencing health system transformations, by bringing forward practical solutions to government that reflect the needs of their members, often frontline clinicians. PAs strategically seek opportunities for collaboration with stakeholders that can amplify their message. Conclusion: Insights from this work could support health system leaders, policymakers, and researchers in leveraging the role of PAs in health system transformations via strategic collaboration.